Transformation of Islamic Aesthetic Symbols in Contemporary Da’wah Media: a Hermeneutic Review of Gadamer and Ricoeur - Asep Deny Firmansyah; Helmawati Helmawati; Iyad Suryadi (IAIN SYEKH NUR JATI, 2025)
This research analyses how contemporary da’wah art reinterprets Islamic aesthetics through a dialectic between traditional symbols and digital visual innovation. Using the hermeneutic approach of Hans-Georg Gadamer and Paul Ricoeur, this study explores the dynamics of meaning that emerge from the interaction between Islamic visual texts and the modern socio-cultural context. Data were obtained through observation of digital-based da’wah artworks and visual documentation on various media platforms, then analysed using the fusion of horizons and interpretative arc models. The results show that symbols such as calligraphy, geometry, and arabesque have transformed meaning through the digital medium without losing their theological value. This reinterpretation not only expands the aesthetic horizons of da’wah but also increases the relevance of Islamic messages for the digital generation. However, integrating artistic form and theological constraints remains a significant challenge in maintaining authenticity. This study emphasises the importance of collaboration between artists, scholars, and academics to develop innovative, communicative, and spiritually valid models of da’wah art.